Delayed Neutron Detection with graphite moderator for clad failure detection in Sodium-Cooled Fast Reactors. (June 2016) - Rohée, E.; Coulon, R.; Jammes, C.; Filliatre, P.; Normand, S.; Carrel, F.; Lainé, F.; Hamrita, H.
Abstract: In order to meet clean core challenges in Sodium-Cooled Fast Reactors (SFR), specific attention is paid to the cladding integrity. To monitor this integrity, Delayed Neutron Detection (DND) systems are implemented. During clad failures, neutron precursor fission products (mainly halogens: 137 I, 87 Br, 88 Br) escape into the primary coolant. The detection of these precursors through their delayed neutron emission ensures a diagnosis on clad failures events. In DND systems, 3 He proportional counters are selected as the best available technology for neutron detection purposes. Associated with 3 He counters, polyethylene blankets are required in order to thermalize neutrons. The first part of this study is dedicated to the optimization of the DND device by Monte-Carlo simulations in order to improve the detection capability. This optimization focuses on the device design presenting a graphite based alternative to polyethylene blankets in order to remove photoneutron noise from 2 D(γ, n) reactions in polyethylene in presence of a high 24 Na activity (emission of gamma rays at 2.75 MeV). The experimental part of this study is devoted to the validation of a measuring station including an 3 He counter with carbon for neutron moderation. Both Monte-Carlo simulations and experimental results highlight the potential for a low-noise DND system based on graphite moderation.